PENGGUNAAN BASIS AKRUAL DALAM LAPORAN KEUANGAN PEMERINTAH KABUPATEN WATAMPONE - Rustan Rustan; Muhammad Chaikal (Universitas Muhammadiyah Makassar, 2019)
Research aims to determine the use of the accrual base in the financial statements of Watampone District government. The approach used in this research is a qualitative approach. The approach used in this research is a qualitative approach. The research object is located in the research location of the Office of Financial management and regional assets. While the time of this research will be implemented for 2 (two) months. The types of data used in this research are qualitative data, while the source of data obtained in this research is a secondary source. The results of this study show that the financial management apparatus in Bone District government has been aware of the accounting of the accrual base government like what. Government strategy in applying accounting base accrual has been running well in the district of BPKAD Bone and one of the constraints of the preparation of the accrual-based financial statements that are still turtles